The evolution of supermassive Population III stars - Haemmerlé, Lionel; Woods, Tyrone E.; Klessen, Ralf S.; Heger, Alexander; Whalen, Daniel J. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Supermassive primordial stars forming in atomically cooled haloes at z ∼ 15-20 are currently thought to be the progenitors of the earliest quasars in
Published: 16 November 2017
Gesehen am 19.08.2019